AN ANALYSIS OF INFLUENCE PUBLICATION FINANCIAL YEARLY REPORTING TO SHARE PRICE IN AN INDONESIAN STOCK EXCHANGE - Dwitayanti, Yevi (Jurnal Manajemen dan Keuangan, 2008)
Financial reporting is a report of responsibility of management attainment. Responsibility represent the indicator from management successfulness. Financial reporting usually making by company utilize to provide the information concerning financial position of company and also its change.The Relevant of informations could influence a volume of share commerce stock. For example information about financial statement company, governmental policy, inflation rate, economic situation, mount the rate of interest, and others.Accuracy of publication Time very needing by user of financial statement, user not only require to have the relevant information by financial company reporting prediction and its decision, but information have to be more new brand and not only related to last period. meaningful at the present time Accuracy that information which is using by investor and creditor have to have the character specifically of precisely moment of making of prediction and decision.As for target of doing this research is to test whether there is an annual financial statement publication influence to share price in an Indonesian Stock Exchange.Research method which is doing in this research by study of book and observation. Hypothesis examination done by using test of constructively SPSS. In this research writer test its hypothesis by comparing significancy with the probability value as according to storey;level significancy.From examination result, [in] obtaining conclusion that annual financial statement publication doesnât have influence to share price in an Indonesian Stock Exchange. Because storey;level significancy which is[in yielding equal to 0,212 < 0.05. this matter is happened because of market have anticipated beforehand the event but in enabling caused by a[n other information which strong in comparing with information of financial statement itself.Keyword : Share Price, Financial Statement